Maternal & child health nursing : care of the childbearing & childrearing family - Pillitteri, Adele 4 0 16; Tscheschlog, Beverly Ann.; 5 (Philadelphia : Lippincott Williams & Wilkins, 2003)
Accompanying CD-ROM contains a free interactive self-study program of 300 mulitple choice NCLEX-style questions that challenge the student's comprehension and application of important material. Feedback is provided for each answer
Label on accompanying CD-ROM: Student self-study CD-ROM to accompany Pillitteri's maternal & child health nursing, fourth edition / Beverly Ann Tscheschlog
Includes bibliographical references and index
System requirements for accompanying computer disc: IBM-PC or compatible computer; Pentium 100 CPU; 32 MB RAM (64 recommended); Windows 98; Macromedia Flashplayer
Keywords: 2 -- 0; 6; Maternity nursing;Pediatric nursing;Maternal-Child Nursing;Family Health -- 20; 20; 2